Multiscale habitat use by muskrats in lacustrine wetlands - Larreur, Maximillian Roger (Kansas State University, 2018)
The muskrat (Ondatra zibethicus) is an economically and ecologically important furbearer species that occupy wetlands throughout North America. However, populations across the United States (US) are declining and there is little evidence as to the cause of this decline. Wetlands in the upper Midwest, US, are shifting into more homogeneous vegetation states due to an invasive hybrid cattail species, Typha x glauca (hereafter ‘T. x glauca’), outcompeting native vegetation. This hybrid cattail species is now an abundant potential resource for muskrats and has outcompeted native wetland vegetation. I investigated how landscape composition and configuration affected multiscale habitat use by muskrats during the summers of 2016 – 2017. Additionally, I assessed how fetch (impact of wind and wave action), a process dictated by large-scale landscape configuration, influenced muskrat habitat use at a local-scale representing a resource patch. I randomly selected 71 wetland sites within Voyageurs National Park, Minnesota, and used presence/absence surveys to assess site occupancy by muskrats. Each year, multiple surveys were conducted at each site and I used multiseason occupancy modeling to investigate how both local and landscape factors affect site occupancy and turnover. I predicted a positive relationship between local-scale (2 ha) sites, characterized by shallower and less open water, and muskrat occupancy and colonization rates. I also predicted increased occupancy probabilities and colonization rates in wetlands that contain higher amounts of T. x glauca. However, I expected the amount of fetch at each site to negatively influence site occupancy probabilities and colonization rates. At the landscape-scale (2 km), I expected habitat use by muskrats to be positively related to the percentage of T. x glauca and area of wetlands surrounding sites. At the local-scale, muskrats occupied wetlands that contained shallower water depths and less open water. As predicted, site occupancy probabilities were greater in areas with greater amounts of T. x glauca coverage. My results revealed a cross-scale interaction between the severity of fetch impacts and percent of T. x glauca coverage at sites. Muskrats were more likely to colonize areas with greater fetch impacts if there was also greater coverage of T. x glauca at these sites. At the landscape-scale, site-occupancy probabilities were positively influenced by the percent of open water and landscape heterogeneity surrounding each site. My study was the first to document how invasive T. x glauca populations can mitigate negative effects that high wave intensity may have on muskrat spatial distributions. I was also the first to identify multiscale factors affecting the spatial distribution of muskrats in lacustrine ecosystems.
Keywords: Muskrat; Multiscale; Habitat use; Occupancy; Cross-scale; Fetch